Response of Broiler Chickens to Graded Levels of Urea Treated Rice Offal (Global Journal of Science Frontier Research, 2015)
A total of ninety (90) day-old unsexed broiler chickens averaging 50.0 grammes were utilized for the purpose of accessing their response to graded levels of urea treated rice offal. These were randomly allocated into 3 equal groups of 30 birds in each treatment replicated 3 times with each replicate having 10 birds. Three (3) diets designated I, II and III were formulated such that urea treated rice offal was included at 0, 7.5% and 15.0% respectively. The results show that there were no significant differences (P>0.05) in feed intake, weight gain and efficiency of feed utilization among birds fed the control diet and urea treated rice offal based diets. However, feed intake and weight gain were highest with birds fed 15.0% urea treated rice offal compared with those fed the control diet.
Keywords: broilers; chickens; urea; rice offa